Images as data for social science research an introduction to convolutional neural nets for image classification - Webb Williams, Nora ca. 20./21. Jh; Casas, Andreu ca. 20./21. Jh; Wilkerson, John D. 1958- (Cambridge University Press, 2020)
Images play a crucial role in shaping and reflecting political life. Digitization has vastly increased the presence of such images in daily life, creating valuable new research opportunities for social scientists. We show how recent innovations in computer vision methods can substantially lower the costs of using images as data. We introduce readers to the deep learning algorithms commonly used for object recognition, facial recognition, and visual sentiment analysis. We then provide guidance and specific instructions for scholars interested in using these methods in their own research